Type 4 Renal Tubular Acidosis in a Patient With Lupus Nephritis (Iranian Journal of Kidney Diseases, 2014)
Although renal tubular acidosis (RTA) is a rare complication of systemic lupus erythematosus (SLE), type 4 RTA associated with lupus nephritis is extremely rare. A 20-year-old woman presented with malaise and edema in the lower extremities and face. She had multiple lymphadenopathies. There were 20% eosinophil in blood smear and 32% in bone marrow aspiration. Serology revealed positive antinuclear antibody at 1:1000 titer, positive double-stranded DNA antibodies, and low complements C3 and C4 levels. Urinary sediment was active and urinary protein excretion was 4.8 g/d. The SLE Disease Activity Index score was 23. A high SLE Disease Activity Index scores was proposed as a potential risk factor for type 4 RTA. Type 4 RTA may complicate SLE, and specifically, patients with high SLEDAI scores and lymphadenopathy may pose a high risk. Our patient responded successfully to immunomodulatory therapy.